PENEGAKAN HUKUM TERHADAP PERUSAHAAN YANG MELAKUKAN PENAHANAN IJAZAH BERDASARKAN PASAL 374 KUHP TENTANG PENGGELAPAN OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Sori Muda Siregar; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Some companies implement agreements that require workers to depositdiplomas as job security on the grounds of contract insurance that is because employeeswho often feel uncomfortable working and exit before the contract expires. The awardof this diploma is done by the company with the reason that its employees can work atleast until the contract of work contract is finished so as not to harm the company.Another reason that companies often use is to proof the seriousness of workers willimplement the work agreement well during the work period. If it does not meet thecontents of the contract agreement, the company will impose administrative sanctionson the workers. The purpose of this study is to determine the process of investigation ofcompanies that conduct diploma detention in Pekanbaru and law enforcement againstcompanies that make custody of diploma under article 374 of the Criminal Code aboutembezzlement by Pekanbaru City Police.The type of this research is sociological law research with case study methodthat is used to research the truth of an event that happened by observing an object in theform of state, individual and community. whereas if viewed from the nature of thisresearch is descriptive. This research uses primary data and secondary data.The results of this study is the process of investigation of companies conductingdetention of diplomas in Pekanbaru still in the stage of investigation. The requirementof the latest education certificate is usually requested by the company when theprospective worker is accepted to work in the company as a guarantee that the workerdoes not leave before the contract expires. The request for this diploma is then pouredinto a work agreement containing the terms of employment, rights and obligations ofthe parties including the submission of a diploma guarantee to be signed by the workersand the company. If the employee has resigned by submitting a monthly resignationletter (one month notice), and has fulfilled the conditions stipulated in the submission ofresignation, then the agreement contained therein shall be expired. This enables theparties to return the rights of each party requested including a diploma. But there arestill many companies that violate agreements that have been agreed so that this isdetrimental to employees. Law enforcement against companies that conduct diplomadetention under section 374 of the Criminal Code on embezzlement by Pekanbaru CityPolice Force. The detention of a diploma by a company is a fraud. Fraud committed bythe company in the possession of goods in the form of a diploma of workers due to aworking relationship may be subject to a five-year criminal penalty.Keywords: Law enforcement, detention of diploma.